Complex polymorphisms in the plasmodium falciparum multidrug resistance protein 2 gene and its contribution to antimalarial response - Veiga, Maria Isabel (2015)
Plasmodium falciparum has the capacity to escape the actions of essentially all antimalarial drugs. ATP-binding cassette (ABC) transporter proteins are known to cause multidrug resistance in a large range of organisms, including the Apicomplexa parasites. P. falciparum genome analysis has revealed two genes coding for the multidrug resistance protein (MRP) type of ABC transporters: Pfmrp1, previously associated with decreased parasite drug susceptibility, and the poorly studied Pfmrp2. The role of Pfmrp2 polymorphisms in modulating sensitivity to antimalarial drugs has not been established. We herein report a comprehensive account of the Pfmrp2 genetic variability in 46 isolates from Thailand. A notably high frequency of 2.8 single nucleotide polymorphisms (SNPs)/kb was identified for this gene, including some novel SNPs. Additionally, we found that Pfmrp2 harbors a significant number of microindels, some previously not reported. We also investigated the potential association of the identified Pfmrp2 polymorphisms with altered in vitro susceptibility to several antimalarials used in artemisinin-based combination therapy and with parasite clearance time. Association analysis suggested Pfmrp2 polymorphisms modulate the parasite's in vitro response to quinoline antimalarials, including chloroquine, piperaquine, and mefloquine, and association with in vivo parasite clearance. In conclusion, our study reveals that the Pfmrp2 gene is the most diverse ABC transporter known in P. falciparum with a potential role in antimalarial drug resistance.